Continuous preparation of dual-mode luminescent LaPO4:Tb3+, Yb3+ nanoparticles by reactive flash nanoprecipitation. (12th October 2021) - Fan, Wenting; Zhao, Fang; Dou, Jiahong; Guo, Xuhong
Graphical abstract: Highlights: LaPO4 :Tb 3+, Yb 3+ nanocrystals were synthesized by flash nanoprecipitation. The nanocrystals exhibited both upconversion and downconversion luminescence. A cost-effective MIVM (multi-inlet vortex mixer) reactor was home-made. Good mixing in the MIVM reactor was validated both experimentally and numerically. Abstract: The efficient and scalable synthesis of lanthanide-doped NPs, which exhibit down- and upconversion luminescent properties simultaneously, is still a main challenge that are hindering their adoption. Herein, we employed a facile method, i.e. reactive flash nanoprecipitation, to fabricate dual-mode luminescent lanthanide phosphate (LnPO4 ) NPs: lanthanum phosphate (LaPO4 ) co-doped with Tb 3+ and Yb 3+ . The lanthanide source streams and phosphate ion source streams were efficiently mixed in a multi-inlet vortex mixer reactor, and the use of a stabilizer was found to facilitate the formation of uniformly-dispersed LnPO4 nanocrystals. It is demonstrated that the annealed LnPO4 NPs exhibited intense down- and upconversion emission under UV and NIR irradiation, respectively. Notably, through adjusting the LnPO4 to stabilizer mass ratio, the NP diameter could be tuned in a range between 50 and 200 nm, and the composition of LaPO4 :Tb 3+, Yb 3+ NPs could be easily tuned by adjusting the flow rate ratio of the feed streams.